Pengaruh Beban Kerja, Lingkungan Kerja dan Kompensasi Finasial Terhadap Kepuasan Kerja Pegawai Perum Bulog Cabang Sikur Lombok Timur - Monika, Baiq Livia; Suryatni, Mukmin (Postgraduate, University of Mataram, 2025)
This research aims to determine the effect of workload, work environment, and financial compensation on job satisfaction of employees at Perum Bulog Branch in Sikur East Lombok. The background of this study arises from the fluctuations in the achievement of distribution targets for commodities, which are suspected to be caused by low job satisfaction among employees, influenced by excessive workload, an unfavorable work environment, and inadequate compensation. This research uses a quantitative approach with a causal associative research type. The research sample consists of 64 permanent employees and uses census technique. Data were collected through questionnaires and interviews, then analyzed using multiple linear regression. The research results show that workload has a significant negative effect on job satisfaction, while the work environment and compensation have a significant positive effect. This indicates that job satisfaction can be improved by better distributing tasks proportionally, creating a comfortable work environment, and providing appropriate and fair compensation. The implication of this study is the need for the management of Perum Bulog Branch Sikur to review its employment policies in order to increase productivity and achieve the company's targets.